Anthropometric Indicators of the Cardiometabolic Risk, Muscle Strength, and Functional Capacity of Schoolchildren with Intellectual Disabilities during Lockdown in Chile - Claudio Farías-Valenzuela; Gerson Ferrari; Sebastián Espoz-Lazo; Paloma Ferrero-Hernández; Emilio Jofré-Saldia; Sebastián Álvarez-Arangua; Carlos Poblete-Aro; Andrés Godoy-Cumillaf; Cristian Cofre-Bolados; Pedro Valdivia-Moral (Children, 2022)
Lockdown due to the COVID-19 pandemic has negatively impacted the social, psychological, and physical well-being of the world population. In the case of people with intellectual disabilities, the impact of lockdown on their physical condition and functionality is not completely clear. This study aimed to determine the effects of COVID-19 lockdown on the anthropometric indicators of cardiometabolic risk, muscle strength, and functionality on schoolchildren with intellectual disabilities. The sample was composed of 132 students of both sexes (n = 74 pre-lockdown; n = 58 lockdown) belonging to two special education centers from the Metropolitan Region of Santiago, Chile. Our results showed significant reductions (p ≤ 0.05) in absolute and relative handgrip strength, as well as in functionality, when comparing pre-lockdown and lockdown measurements, with a greater loss in girls than boys. The design and implementation of physical exercise programs centered on strength training are necessary for the physical and functional reconditioning of this population. These programs need to be implemented in special education centers considering the general well-being, quality of life and work needs of people with intellectual disabilities.